Pemahaman Manajemen Perjalanan Ibadah Haji: Dari Persiapan Di Tanah Air Hingga Kepulangan - susetyo, aris (Jurnal Inovasi Pengabdian Masyarakat, 2025)
The Hajj pilgrimage is one of the pillars of Islam that must be carried out by every Muslim who is able, both physically, mentally, administratively, and financially. Hajj has the meaning as a response to the call of Allah SWT, with the aim of carrying out a series of practices in the Baitullah. As a worship that involves traveling across countries, hajj involves various complex aspects, such as preparation in the homeland, implementation in the holy land, to returning to the homeland. One of the most important things in carrying out the hajj pilgrimage is travel management, which includes schedule planning, document arrangements, transportation, accommodation, and managing the health and safety of pilgrims. However, many pilgrims do not understand the importance of travel management, so they have the potential to face various obstacles, such as document incompatibility, delays, physical fatigue, and suboptimality in carrying out worship. Therefore, counseling activities regarding the management of the hajj pilgrimage journey are very much needed to improve the physical, mental, and logistical readiness of pilgrims. Through lectures and discussions, this counseling aims to provide an understanding of the steps that must be taken at each stage of the hajj journey, starting from preparation in the homeland, departure, implementation of the pillars of hajj, to returning to the homeland. It is expected that through this activity, the congregation can minimize the obstacles faced and carry out the Hajj pilgrimage more optimally, safely, and smoothly.